PENINGKATAN KEMAMPUAN MATEMATIKA DASAR MELALUI MUSIC AND MOVEMENT - Amna N Noho (LPPM Universitas Muhammadiyah Gorontalo, 2018)
The purpose of this study was to determine whether the basic math skill students 5-6 years old can be improved through music and movement. This research was conducted at TKIT Ibnu Sina Duren Sawit, East Jakarta Timur, with as many as 27 students study subjects. The study was conducted in two cycles and accompanied by 2 teachers who act as observers, method action research. Data collected through observation and interviews as well as qualitative and quantitative data analysis. Qualitative data were analyzed by comparing the students’ grades in cycle 1 and cycle 2 while the qualitative data was analized by data reduction, display data, and conclusion. The results showed an increase in students’ basic math skill through music and movement. In cycle 2 the development of the mathematical aspects of general intelligence has increased 23% from the initial conditions before the study, in wich each indicator increased by 52% compared to the time of observation. Based on data analysis, it can be concluded that the students’ basic math skill can be improved through music and movement. It is thus suggested to kindergarten teachers to use music and movement in order to improve the learning basic math skill of students. Tujuan penelitian ini adalah mengetahui apakah kemampuan dasar matematika siswa usia 5-6 tahun dapat ditingkatkan melalui kegiatan music and movement . Penelitian ini dilakukan di TKIT Ibnu Sina Duren Sawit, Jakarta Timur, dengan sebanyak 27 siswa subjek penelitian. Penelitian dilakukan dalam dua siklus dan didampingi oleh 2 orang guru yang bertindak sebagai pengamat, metode penelitian tindakan. Data dikumpulkan melalui observasi dan wawancara serta analisis data kualitatif dan kuantitatif. Data kuantitatif dianalisis dengan membandingkan nilai siswa dalam siklus 1 dan siklus 2 sedangkan data kualitatif dianalisis dengan reduksi data, data tampilan, dan kesimpulan. Hasilanya menunjukkan peningkatan kemampuan matematika dasar siswa melalui kegiatan music and movement . Pada siklus 2 perkembangan aspek matematika dasar telah meningkat 23% dari kondisi awal sebelum penelitian, yang mana setiap indikator meningkat sebesar 52% dibandingkan dengan waktu pengamatan. Berdasarkan analisis data, dapat disimpulkan bahwa kemampuan matematika dasar siswa dapat ditingkatkan melalui kegiatan music and movement. dengan demikian disarankan kepada guru TK untuk menggunakan music and movement dalam rangka meningkatkan kemampuan matematika dasar siswa.